2012 4th IEEE RAS &Amp; EMBS International Conference on Biomedical Robotics and Biomechatronics (BioRob) 2012
DOI: 10.1109/biorob.2012.6290782
|View full text |Cite
|
Sign up to set email alerts
|

3D femur reconstruction using a robotized ultrasound probe

Abstract: Three-dimensional reconstruction of images is a fundamental procedure in medical imaging because it allows to build virtual models of anatomical units of the human body, useful in several areas, such as in surgical navigation. This paper presents a non freehand Ultrasound acquisition system for human femur reconstruction where the probe displacement and position are accurately controlled by an anthropomorphic arm robot. The aim of this system is to acquire a sequence of 2D parallel cross-sections evenly spaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Offline 3D reconstruction systems are often used in ultrasound examinations and can be optimized by the usage of robotic systems moving the ultrasound probe [24]. Moreover, it is reported that a non-freehand ultrasonic acquisition system for human femur reconstruction was developed [25]. In this work we use 3D reconstruction to compare free-hand data acquisition with data collected using the hereproposed system.…”
Section: A State Of the Art In Ultrasound Automationmentioning
confidence: 96%
“…Offline 3D reconstruction systems are often used in ultrasound examinations and can be optimized by the usage of robotic systems moving the ultrasound probe [24]. Moreover, it is reported that a non-freehand ultrasonic acquisition system for human femur reconstruction was developed [25]. In this work we use 3D reconstruction to compare free-hand data acquisition with data collected using the hereproposed system.…”
Section: A State Of the Art In Ultrasound Automationmentioning
confidence: 96%
“…Image-Guided Surgery (IGS) means the accurate correlation and mapping of the operative field to a pre-operative image or intra-operative (e.g., ultrasound [5], fluoroscopy) data set of the patient via sensory information (optical, mechanical or electromagnetic tracking). IGS provides better equipment positioning accuracy or guidance of mechatronic systems, and has primarily been used in neurosurgery, pediatrics, orthopaedics and Ear, Nose and Throat (ENT) surgery-domains that have been more exposed to novel technology [6].…”
Section: The Rise Of Robotic Technology In the Medical Fieldmentioning
confidence: 99%
“…The ontological model obtained, i.e., its formal description, is of major interest to setup a service robot, e.g., a robot manipulator, that will perform the surgery in a co-worker scenario with the surgeon, delivering the expected increased accuracy and precision. This work is developed under the HIPROB (http://www.echord.info/wikis/website/hiprob) [5] and ECHORD projects (http://www.echord.info/wikis/website/home).…”
Section: B Ontology For Orthopaedicsmentioning
confidence: 99%
See 2 more Smart Citations